Knowledge Attitude and Practice Survey on The Various Impression Techniques for Custom Made Post Among Specialist and Dental Practitioners - Kannan, Aarthi; PM, Vikhashini (Journal of Neonatal Surgery, 2025)
Introduction: A post and core crown is a form of dental restoration used when there isn't enough healthy tooth tissue left to support a traditional crown. A post is cemented into a prepared root canal to hold a core repair and the final crown in place. The advantage of putting a post into a root canal is that the crown is more likely to remain in place. Materials and method: A well-structured questionnaire comprising 13 questions covering the socio-demographic information, knowledge, attitude, perception was framed, administered and circulated to college students through an online survey link. The sample size was 100 undergraduate students and postgraduate students. The questions were carefully studied and the corresponding answers were marked by the participants. Result: Survey on the various impression techniques for custom made post’s gave the result as 53% of the population wall between the age group of 25-30 years, 27% of the population between the age group of 20-25 years and the rest were about 30 years. Among the total population 59% preferred composite resin 30% preferred GIC where the rest preferred amalgam as the core foundation. Chi square test shows p value as 0.037 ( p< 0.05). Hence it is statistically significant. Conclusion: In conclusion, it was evident that the majority of the participants were aware of the impression materials used and practiced it in their daily practice. Most of them stated the use of a prefabricated post system made of composite resin or ceramic materials necessitates root canal preparation to the post's size and shape. And most of the practitioners preferred composite resin as core foundation